Belajar Moderasi Beragama dari Pesantren - Rahmat, Ali (Fakultas Agama Islam Universitas Billfath, 2024)
Currently, we are faced with a reality of social life that has the potential to undermine the ideology of the nation and state. This is caused by several factors, such as: the emergence of subjective truths regarding religious understanding and the growth of excessive religious thought patterns and attitudes. The aim of this research is to find out that the concept of religious moderation exists at the Annuqayah Islamic boarding school. The approach used in this research is a qualitative approach. The type of research is a case study. Data and information collection techniques use interview, observation, FGD and documentation methods. Meanwhile, the data analysis method uses descriptive analysis. The research results show that the concept of religious moderation found in the Annuqayah Islamic boarding school is in the form of concepts, principles, values ​​and practices that reflect moderation. Annuqayah Islamic Boarding School understands Islam as a religion that stands in the middle. This moderate attitude also means keeping oneself from acting ifrath and tafrith. The principles of religious moderation in Annuqayah are tawassuth (middle), i'tidal (upright and proportional), tasamuh (tolerant), tawazun (balance); musawah (egalitarian). Kiai Annuqayah's strategy in establishing religious moderation is as follows; amaliyah ubudiyah, amaliyah diniyah, amaliyah ijtimaiyyah, and amaliyah siyasiyyah.